Physical Activity After Percutaneous Coronary Intervention for Chronic Total Occlusion and Its Association With Health Status. Issue 7 (2nd April 2019) - Peri‐Okonny, Poghni A.; Spertus, John A.; Grantham, J. Aaron; Gosch, Kensey; Kirtane, Ajay; Sapontis, James; Lombardi, William; Karmpaliotis, Dimitri; Moses, Jeffrey; Nicholson, William; Salisbury, Adam C.
Abstract : Background: Patients with chronic total occlusion (CTO) may not participate in regular exercise because of refractory angina. Exercise participation after percutaneous coronary intervention (PCI) for CTO (CTO PCI) and the association of exercise with health status after CTO PCI is unknown. Methods and Results: Overall, 1000 patients enrolled in the Outcomes, Patient Health Status, and Efficiency in Chronic Total Occlusion OPEN CTO is a registry were asked about participation in regular exercise at baseline and 12 months after CTO PCI, and the frequency of exercise (<1, 1–2, ≥3 times/week) was collected among exercisers. Health status was assessed using the Seattle Angina Questionnaire (SAQ). Multivariable regression assessed 12‐month health status change across 4 groups defined by exercise frequency at baseline and 12 months after CTO PCI (no regular exercise at baseline and 12 months, reduced, increased, and consistent exercise at 12 months). Among 869 patients with complete exercise data, the proportion that exercised regularly increased from 33.5% at baseline to 56.6% 12 months after CTO PCI ( P <0.01). Predictors of regular exercise at 12 months included baseline exercise, smoking, baseline and increase in SAQ scores for angina frequency, physical limitation, quality of life, and summary. After multivariable adjustment, consistent or increased exercise frequency was associated with significantly greater improvement in SAQ scores for angina frequency, physical limitation, quality of life, and summary ( P <0.01). Conclusions: Participation in regular exercise increased significantly 12 months after CTO PCI, and patients who had greater health status benefit after PCI were more likely to exercise regularly at 12 months. CTO PCI may enable coronary artery disease patients with limiting symptoms to engage in regular exercise and to support better long‐term outcomes.